Low Density Lipoprotein Receptor-Related Protein-1 in Cardiac Inflammation and Infarct Healing - Potere, Nicola; Del Buono, Marco Giuseppe; Mauro, Adolfo Gabriele; Abbate, Antonio; Toldo, Stefano (Frontiers in Cardiovascular Medicine, 2019)
Acute myocardial infarction (AMI) leads to myocardial cell death and ensuing sterile inflammatory response, which represents an attempt to clear cellular debris and promote cardiac repair. However, an overwhelming, unopposed or unresolved inflammatory response following AMI leads to further injury, worse remodeling and heart failure (HF). Additional therapies are therefore warranted to blunt the inflammatory response associated with ischemia and reperfusion and prevent long-term adverse events. Low-density lipoprotein receptor-related protein 1 (LRP1) is a ubiquitous endocytic cell surface receptor with the ability to recognize a wide range of structurally and functionally diverse ligands. LRP1 transduces multiple intracellular signal pathways regulating the inflammatory reaction, tissue remodeling and cell survival after organ injury. In preclinical studies, activation of LRP1-mediated signaling in the heart with non-selective and selective LRP1 agonists is linked with a powerful cardioprotective effect, reducing infarct size and cardiac dysfunction after AMI. The data from early phase clinical studies with plasma-derived 1-antitrypsin (AAT), an endogenous LRP1 agonist, and SP16 peptide, a synthetic LRP1 agonist, support the translational value of LRP1 as a novel therapeutic target in AMI. In this review, we will summarize the cellular and molecular bases of LRP1 functions in modulating the inflammatory reaction and the reparative process after injury in various peripheral tissues, and discuss recent evidences implicating LRP1 in myocardial inflammation and infarct healing.